Prognostic Factors Affecting Survival in Malignant Pleural Mesothelioma: Analysis of 125 Subjects. Issue 1 (January 2014) - Komurcuoglu, Berna; Cirak, A Kadri; Kirakli, S Cenk; Polat, Gulru; Yucel, Nur; Usluer, Ozan; Erer, Onur; Balci, Gunseli; Gayaf, Mine; Guldaval, Filiz; Aktogu, Serir; Guclu, Salih; et al.
Aim of the Study: Determining the pre-treatment prognostic factors in malignant pleural mesothelioma is important in terms of estimating the course of the disease and selecting patients who are candidate for multimodal therapy. The aim of the study was to determine the prognostic factors affecting survival in patients with malignant pleural mesothelioma. Study Design: One hundred and twenty-five patients who had been diagnosed histologically as having malignant pleural mesothelioma over the past 5 years were evaluated retrospectively. Relationships of survival of the patients with their age, gender, exposure to asbestos, smoking history, platelet, hemoglobin, leukocyte (WBC) and serum LDH values, histology, performance score and stage of disease were examined. Results: Advanced clinical stage, N2 nodal involvement and the presence of distant metastasis were found to be related to survival. Sarcomatous histology was found to be a poor prognostic factor independently of other factors. Conclusions: We showed that histological subtype and stage of disease were the most important parameters in planning the treatment, especially in determining the patients who were candidate for multimodal treatment and in estimating the prognosis.